STUDENT WORKSHEET ORIENTED ON PROJECT BASED LEARNING TO TRAIN STUDENT CREATIVE THINKING SKILLS ON ACID-BASE MATERIAL (Universitas Negeri Surabaya, 2021)
The aim of this research is to determine the feasibility of student worksheet oriented on project based learning (PjBL) to train students' creative thinking skills on acid-base material. The research method referred to the 4D development design that consisting of 4 stages including: (1) define, (2) design, (3) development, and (4) dissemination. This research was limited to development stage. The limited trial was treated to 12 students of eleventh grade of a State Senior High School. Feasibility of worksheet was reviewed from the content validity and the construct validity (aspect of language, presentation, and graph) through validation results of experts, practicality through student activity observation and student response, and effectiveness through creative thinking skills test. Creative thinking skills included four aspects: fluency, flexibility, elaboration, and originality. The data analysis used qualitative and quantitative descriptive analysis methods. The results showed that the developed worksheet was valid in terms of content validity (84.44%) and construct validity (83.63%). Practicality in terms of relevant student activities observation and student responses got percentage of 92.74% and 93.66% in very practical category. The effectiveness of creative thinking skills training in terms of the N-gain score had a percentage of 0.60 in enough category. Key words: worksheet, project based learning, creative thinking skills